Self-Efficacy in the Classroom: A Socio-Cultural Perspective on the Contributing and Detracting Factors - Wall, Christopher (Auckland University of Technology, 2019)
This thesis is an investigation into both self-efficacy and cultural capital in New Zealand classrooms. I believe that there is a useful intersection to be found between these two concepts, and through this thesis I aim to provide teachers and leaders with further knowledge to promote self-efficacy development in their students. I will argue that a strengths-based approach is critical in acknowledging and validating cultural capital, and providing a platform from which self-efficacy can be fostered. I consider that it is pertinent for educational leaders to consider the self-efficacy development of both their students and teachers, in order to increase agency throughout the school. Based on my analysis of the literature it would seem that self-efficacy is highly complex, and difficult to quantifiably measure. I will argue in this thesis, that part of this complexity is due to the socio-cultural nature of the construction, and continuance of self-efficacy. Cultural capital is similarly complex and multifaceted with a very broad spectrum of contributing factors. I will also argue that cultural capital, when considered from a deficit perspective can become a type of cultural distance from prevailing norms. This cultural distance can serve to limit self-efficacy development. A mixed methods approach, situated from a pragmatic research position was adopted to conduct a naturalistic research project. In order to conduct the research I selected two case study schools and one further supplementary school. Initially I surveyed the participants to discover a comparative reference of their levels of self-efficacy. This was followed by in-class observations and semi-structured interviews. The analysis of the data collected suggests that knowledge of the concept of self-efficacy is not widespread. It also suggests efficacy beliefs in the classroom are potentially interrelated, with a reciprocal relationship between the self-efficacy of teachers and students. The voice of the participants also reinforces the literature that suggests self-efficacy development is more effective in differentiated classrooms. I believe that increasing the understanding of self-efficacy, combined with deliberate strategies employed by educational leaders to adopt strengths-based and differentiated approaches will ultimately improve outcomes for a broad demographic of students.
Keywords: Self-efficacy; Cultural capital; Culture; Classroom; Teacher; Efficacy; Bandura; Bourdieu